Gambaran Dukungan Sosial Teman Sebaya dan Efikasi Diri pada Mahasiswa Psikologi yang Mengalami Gangguan Psikologis - Dwijayani, Ni Komang Karmini; Fridari, I Gusti Ayu Diah (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 3 (2021): Volume 1 Nomor 3 Tahun 2021 - Widya Cakra, 2022)
Mental health is an interesting topic to address today. Psychology is a field of science enticing and attracting many enthusiasts. Unfortunately, it has not been supported by improving mental health literacy in the community. There are a lot of stigmas against people who have psychological disorders. High expectations towards psychology can also put pressure on psychology students. In fact, psychological disorders start to be found in university student, including psychology students. This study aims to observe an overview of peer social support and self-efficacy in psychology students experiencing psychological disorders. This study applied qualitative approach with a descriptive case study method with an intrinsic type of case study. The sampling technique used was purposive sampling technique. The study respondents consisted of two girls and one boy in adolescence who were active students with a diagnosis of psychotic and neurotic psychological disorders. Data collection was carried out through semi-structured interviews with data analysis using thematic analysis. The results showed that psychology students with psychological disorders seeking social support through close peers in the Psychology Department. The forms of social support received are emotional, informational, instrumental, and friendship social support. Having self-efficacy tends to be positive, shown by aspects of self-confidence, optimism, responsibility, rational and realistic. Negative self-efficacy was found in students who experienced psychotic disorders in terms of confidence in completing theses, confidence in making decisions, and self-assessment.